(untitled) (Al-Qamar, 2023)
Islam is the religion of peace, prosperity and brotherhood. Our religion guides us in every aspect of the life and it build up high moral values in oneself. The Seerah guides in daily life affairs to tackle in effective way and promotes the culture of forgiveness and tolerances that helps the people focus and reach their destinations. But unluckily, we have abandoned our rich values and we find the society which is highly hit by intolerance like negative behaviors. The research article focuses on the rampant intolerance in the society. What guidance’s are given in Quran and Sunnah about the tolerance? The survey is conducted in Faisalabad district. The male and female aged between 25to 35 years are asked why intolerance is increasing in the society and what its affect are. In the modern era, the moral values are facing the declining trends and, in every field, the love, care, brotherhood, sacrifices etc. like values are diminishing that is provoking intolerance attitudes